Quick Take Off in Spanish - Rosa Mar1a Mart1n (Oxford University Press, 2003)
Ideal for last minute language learning, Quick Take Off In Spanish enables the absolute beginner or the refresher learner to speak and understand Spanish fast, containing all the essential vocabulary, grammar, and pronunciation guidance needed to communicate with confidence. With 150 minutes of audio on 2 CDs or 2 cassettes and an easy-to-follow book, the course covers everything you need, from booking a hotel to travelling around or going shopping, through a variety of quick and simple speaking and listening activities. It includes a quick-reference section so you can dip in and out of your preferred topics, offers tips on Spanish culture, a handy ready-reckoner, and test-yourself assessments. A credit-card-sized survival guide gives you emergency vocabulary at your fingertips, and the light, transparent travel pack means that it's perfect for people on the move: if you're heading off on business or pleasure, you can get to grips with the language on the way to your destination and communicate with confidence from the word go.